2011
DOI: 10.1002/lary.21968
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of head and neck squamous cell carcinoma patients with N3 neck disease treated primarily with chemoradiation versus surgical resection

Abstract: Patients with head and neck squamous cell cancer and N3 neck disease have at least equivalent survival with primary surgical treatment versus primary CRT. Primary surgical resection with appropriate adjuvant therapy should be considered for patients with resectable N3 disease, especially patients with nonoropharyngeal sites. Post-CRT neck dissections did not change the OS of patients with N3 disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…We previously reported our institutional experience regarding clinical outcomes of N3 HNSCC (under review). Similar to other series, we demonstrated 5‐year rates of locoregional and distant control of approximately 75% and 60%, respectively . Further, we demonstrated an improvement in locoregional control with surgery and a trend toward improved survival in patients with p16‐positive oropharyngeal primary tumors.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…We previously reported our institutional experience regarding clinical outcomes of N3 HNSCC (under review). Similar to other series, we demonstrated 5‐year rates of locoregional and distant control of approximately 75% and 60%, respectively . Further, we demonstrated an improvement in locoregional control with surgery and a trend toward improved survival in patients with p16‐positive oropharyngeal primary tumors.…”
Section: Introductionsupporting
confidence: 88%
“…The NCDB does not record whether or not the N3 lymph node is resectable. For patients with N3 HNSCC, the prevalence of unresectable nodal disease has been reported to be approximately 20%‐30% and impacts both disease‐free and overall survival outcomes . Therefore, a sensitivity analysis utilizing assumed prevalence and HRs was performed to assess the impact of the unmeasured nodal confounder on overall survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies that specifically evaluate outcomes of a primary surgical paradigm for N3 OPSCC show similarly high survival rates but are limited by sample size. Sakashita et al reported a 100% 4‐year OS for six patients, and Smyth et al found a 5‐year overall survival of 80% in 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, however, survival outcomes specific to HPV‐related N3 disease are unclear given the relative lack of available data. Many reports of treatment outcomes for N3 neck disease either group multiple head and neck subsites or do not include HPV status if reporting on oropharyngeal primaries . Those that include specifically HPV‐related disease often group N2 and N3 stages for analysis or have a very limited sample size of N3 patients …”
Section: Introductionmentioning
confidence: 99%